Integrated catering training for PKK women empowerment: Production, presentation, and digital promotion - Rahmawati, Fitri; Trilisiana, Novi; Lastariwati, Badraningsih; Rahman, Luthfi Riyadh (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2026)
This community service program was conducted to empower women in PKK Dusun Gondanglegi, Sleman, through integrated vocational training in catering. The program aimed to improve participants' competencies in food production, professional presentation, and digital promotion. The primary reason was a gap between participants' actual capacities and competitive catering standards: 25 active PKK members earned an average monthly revenue of under IDR 500,000, served only local orders, and relied entirely on word-of-mouth marketing, with no digital presence. The program applied competency-based training through three sequential stages: cognitive knowledge on catering management, cost calculation, and entrepreneurship; hands-on practice in menu diversification, plating, and packaging; and digital promotional content creation using smartphones. Evaluation applied the Kirkpatrick Model at two levels: Level 1 measured satisfaction via a 5-point Likert scale (mean = 4.25/5.00), and Level 2 assessed competency mastery through written tests and rubric-based assessments. All four groups achieved the "Excellent" (Istimewa) category with scores between 85-93. The program also led to the formation of a pilot catering business unit receiving three initial orders, demonstrating that integrated multi-competency training yields more sustainable empowerment outcomes than single-intervention approaches.
Keywords: catering business; digital marketing; vocational training; women empowerment